2021
DOI: 10.1186/s12711-021-00658-7
|View full text |Cite|
|
Sign up to set email alerts
|

Opportunities and limits of combining microbiome and genome data for complex trait prediction

Abstract: Background Analysis and prediction of complex traits using microbiome data combined with host genomic information is a topic of utmost interest. However, numerous questions remain to be answered: how useful can the microbiome be for complex trait prediction? Are estimates of microbiability reliable? Can the underlying biological links between the host’s genome, microbiome, and phenome be recovered? Methods Here, we address these issues by (i) devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…The abundances of some genera were significantly correlated at the genetic level with feed efficiency traits, suggesting opportunities to use microbiota derived traits as proxies of feed efficiency in breeding. Following these results, some authors proposed to use the microbiota information to improve feed efficiency traits ( Weishaar et al, 2020 ; Christensen et al, 2021 ; Pérez-Enciso et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The abundances of some genera were significantly correlated at the genetic level with feed efficiency traits, suggesting opportunities to use microbiota derived traits as proxies of feed efficiency in breeding. Following these results, some authors proposed to use the microbiota information to improve feed efficiency traits ( Weishaar et al, 2020 ; Christensen et al, 2021 ; Pérez-Enciso et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm this, the predictive ability of the Micro+Gen model to predict phenotypes should be estimated and compared with that of the Micro and Gen models. Using simulated phenotypes in cattle, Pérez-Enciso et al [ 38 ] showed that including both microbiota and genome data in the model could increase the predictive accuracy by 50%. In addition, such comparisons could confirm if a model that fits jointly microbiota and genomic effects can help better predict digestive and feed efficiency phenotypes than models fitting each effect separately.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiality estimates may be affected by the underlying model used for the distribution of the microbial effects, or by the estimation framework. Numerous methods exist to estimate , such as the Bayes C hypotheses of mixtures of distributions with different variances [ 38 ], MBLUP [ 18 ], and Bayesian regression [ 12 , 15 , 40 , 41 ]. Pérez-Enciso et al [ 38 ] compared estimates obtained with Bayes C and Bayesian RKHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors noticed the following two errors: Figures 1 and 2 are swapped, but the legends and figure numbers are correct, that is, the legend indicated for Figure 1 is in the right place but corresponds to Figure 2, and vice versa; and In the Funding section, the statement: MPE is funded by Ministry of Science and Innovation-State Research Agency (AEI) Grant PID2019-108829RB-I00 is incomplete. The correct paragraph should be: MPE is funded by the Ministry of Science and Innovation-State Research Agency (MICIN/AEI/10.13039/501100011033) Grant PID2019-108829RB-I00.…”
Section: Correction To: Genet Sel Evol (2021) 53:65 Https://doiorg/101186/s12711-021-00658-7mentioning
confidence: 99%